CAMPUR KODE DALAM PERCAKAPAN GRUP KERJA WHATSAPP KARYAWAN - Cita, Cita Dwi Yuniasih; Rani Gustiasari, Dewi (Universitas Terbuka, 2023)
This research was conducted to provide information to readers regarding the form of code mixing, as well as how the code interference event can occur. This is also used as a learning for writers, in training analytical skills, and is expected to be used as something that can inform readers. This study also contains what factors cause code interference in Whatsapp workgroup conversations in PT employees. Alita Praya Mitra. The research methods used are qualitative methods, identification and recording techniques, as well as classifying and explaining data to analyze conversation data. The results of the analysis that have been examined, there is a mixture of codes when discussing between employees and employees, and between employees and superiors during working hours. The factor that influences the occurrence of code interference is the number of employees who carry out work from home / Work From Home (WFH) and the use of code mix can give a formal impression as a form of employee professionalism in their work.